PROTECTION OF CRIME VICTIMS’ RIGHTS IN THE AUSTRALIAN FEDERATION - Turaeva Dilnoza Rustambaevna (Sciental Journals Publishing, 2026)
This article analyzes, from a scholarly legal perspective, the legal and institutional mechanisms aimed at protecting the rights and legitimate interests of victims of crime in the states of the Australian Federation. The study examines the legal status of victims, state-guaranteed compensation schemes, forms of victim participation in criminal proceedings, as well as institutions of restorative justice. Australia’s experience is subjected to a comparative analysis with international standards.
Keywords: Victim, criminal procedure, compensation, Victim Impact Statement, restorative justice, Australia.